Role of eNOS in water exchange index maintenance-MRI studies; Journal of Physics: Conference Series; Vol. 886 : Magnetic resonance imaging in biomedical research - Atochin D. N. Dmitry Nikolaevich; Litvak M. M. Maksim Mikhaylovich; Huang Sh. Shuning; Kim Y. R. Young Ro; Huang P. L. Paul Lee (2017, 2017)
Title screen